2016
DOI: 10.1007/s11130-016-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Fructans from Agave tequilana with a Lower Degree of Polymerization Prevent Weight Gain, Hyperglycemia and Liver Steatosis in High-Fat Diet-Induced Obese Mice

Abstract: Fructans from agave have received specific attention because of their highly branched fructan content. We have previously reported that the degree of polymerization (dp) influences their biological activity. Therefore, the aim of this study was to investigate the effect of unfractionated and fractionated fructans (higher and lower dps) from Agave tequilana in high-fat diet-induced (HFD) obese mice. Fructans with a lower dp (HFD+ScF) decreased weight gain by 30 %, body fat mass by 51 %, hyperglycemia by 25 % an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
(36 reference statements)
2
24
0
2
Order By: Relevance
“…Azul, reconocida por el contenido alto de inulina (9) . Se ha documentado en estudios in vitro el uso de inulina de achicoria como sustrato energético para bacterias ácido lácticas (BAL) (10) ; pero las investigaciones con inulina de agave son escasas y se han realizado in vitro (11,12,13) e in vivo (14,15,16) .…”
Section: Introductionunclassified
“…Azul, reconocida por el contenido alto de inulina (9) . Se ha documentado en estudios in vitro el uso de inulina de achicoria como sustrato energético para bacterias ácido lácticas (BAL) (10) ; pero las investigaciones con inulina de agave son escasas y se han realizado in vitro (11,12,13) e in vivo (14,15,16) .…”
Section: Introductionunclassified
“…On the other hand, earlier investigations showed that mice fed with standard or high-fat diets with agavins of low DP led to body weight loss [ 10 , 11 , 12 ]. However, the microbial mechanisms remain unclear [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, earlier investigations showed that mice fed with standard or high fat diet with agavins of low DP led to a body weight loss [10][11][12]. However, the microbial mechanisms remain in unclear [12,13].…”
Section: Introductionmentioning
confidence: 99%